Kaanduri and other stories - Dash Benhur; Das Bikram K Tr (Hyderabad Orient Blackswan, 2015)
The tales in Kaanduri and Other Stories, selected from the writings of Jitendra Narayan Dash (whose pen name is Dash Benhur) reveal his wide range. Small surprises and poignant discoveries about relationships account for the appeal of these stories, occasionally marked by humour, which convey the flavour of life among generally the middle and lower classes of Odisha. This volume of nineteen stories will appeal to general readers and readers of Indian fiction in translation and will be a useful guide for students of Translation Studies. The stories have been deftly translated from the Odia by Prof. Bikram K. Das.
Keywords: Indian English Fiction; Indian English Novel; Indian English Small Stories; Odia Tr in English